1991
DOI: 10.7863/jum.1991.10.6.295
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adnexal masses with transvaginal color ultrasound.

Abstract: We evaluated 14,317 asymptomatic or minimally symptomatic women for ovarian carcinoma with transvaginal color Doppler ultrasound. The resistance index was calculated for at least five separate cardiac cycles in each case, and the mean was calculated. We discovered 624 benign adnexal masses: in every case except one the resistance index was >0.40. There were 56 malignant adnexal masses, 16 of which were stage I ovarian cancers. Neovascularization was found in six 0 varian carcinoma is the major lethal gynecolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
67
1
13

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(83 citation statements)
references
References 2 publications
2
67
1
13
Order By: Relevance
“…-5,12,13 Recently, color flow Doppler imaging has been shown to aid in identifying the cause of adnexal lesions in women beyond adolescence.7-. 9 Fleischer and colleagues 7 have suggested that waveforms and pulsatility indices can help to separate benign and malignant lesions in women. These authors noted that malignant masses tended to have abnormal flow centrally and lower pulsatility indices (mean less than 1.0), whereas benign lesions had peripheral flow and higher pulsatility indices (mean greater than 1.0).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…-5,12,13 Recently, color flow Doppler imaging has been shown to aid in identifying the cause of adnexal lesions in women beyond adolescence.7-. 9 Fleischer and colleagues 7 have suggested that waveforms and pulsatility indices can help to separate benign and malignant lesions in women. These authors noted that malignant masses tended to have abnormal flow centrally and lower pulsatility indices (mean less than 1.0), whereas benign lesions had peripheral flow and higher pulsatility indices (mean greater than 1.0).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in women have attempted to differentiate ovarian mass lesions on the basis of flow patterns on color Doppler ultrasonography?- 9 The lesions in these series differ significantly from those seen in childhood, which limits the usefulness of the data. The purpose of this study is to evaluate the usefulness of transabdominal color Doppler ultrasonography in adolescent girls for the diagnosis of painful ovarian masses based on the pattern of blood flow.…”
mentioning
confidence: 99%
“…The visualization of the ovaries by transvaginal sonography in our study was 983 in premenopausal women (7,495) and 953 in postmenopausal women (1,125). The high rate of visualization in the premenopausal ovaries can be explained by the presence of ovarian follicles, which act as a landmark to visualize the ovary.…”
mentioning
confidence: 94%
“…While grey scale sonography is highly sensitive in identifying ovarian cancer, its diagnostic specificity has been poof. In an attempt to improve the specificity of ultrasound, the use of color Doppler sonography 2,[11][12][13]19,22,25,27 in addition to grey scale imaging has been proposed. In present study, 70 patients were evaluated using morphologic scoring system 14,21,26,28,30 proposed by JP Lerner et al and colour flow directed Doppler measurements were taken.…”
Section: Statistical Analysis Of Pulsatility Indexmentioning
confidence: 99%
“…The minority of patients discovered with early stage disease have 5year survival rate of 80-90%. There are various screening methods 15 for detection of ovarian cancer like bimanual pelvic examination, ultra sound examination (TVS and TAS) 3,5,7,10,23,28,30 with or without colour Doppler flow imaging 2,[11][12][13]17,19,22,25,27,29 and measurement of various circulating proteins like CA 125. 1,6,8,20 In analyzing the screening test by measuring CA 125 level and performing transvaginal ultrasound examination 26 appears to provide the highest specificity and positive predictive value for the detection of ovarian cancer.…”
mentioning
confidence: 99%